Towards real-time interactive visualization modes of molecular surfaces: examples with udock - Levieux, Guillaume; Montes, Matthieu (2015 IEEE 1st International Workshop on Virtual and Augmented Reality for Molecular Science (VARMS@IEEEVR), 2015)
In the present work, we describe and discuss two interactive visualization techniques recently added to the Udock software. First, we propose to display a spherical projection of the protein's molecular surface properties. The resulting 2D map allows to get in one glance a global view of the protein. Second, we propose to let the user choose a specific level of detail when visualizing the protein's 3D surface. We describe a simple smoothing algorithm that achieves this goal in real time. These techniques are designed to enhance the usability of molecular visualization and interactive simulation software.